High Biodiversity and Low Dominance in Insect Species on Marsegu Island: A Case Study: Keanekaragaman Hayati Tinggi dan Dominasi Rendah Spesies Serangga di Pulau Marsegu: Studi Kasus - Berlindus Savdurin; Fransina Latumahina; Cornelia Wattimena (Academia Open, 2023)
This study aimed to assess the diversity and abundance of insect species in the coastal forest of Marsegu Island in the Western Seram Regency. The data was collected using an exploratory method, which involved direct observation and sampling in the field between October 2020 and the completion of the study. A total of 321 individuals representing 20 species from six orders (Orthoptera, Hemiptera, Lepidoptera, Coleoptera, Diptera, Aranae) were identified, distributed across 20 families. The Diptera family Muscidae was most commonly found. The insect diversity index (H') was 4.371, indicating high species diversity within the region. The evenness index (E) was 0.931, suggesting that no single family dominated the population due to a balanced ecosystem. The dominance index was 0.155, implying low dominance and equitable abundance among species. The findings emphasize the importance of Marsegu Island's ecological balance, which may be threatened by chemical interventions. It is crucial to conserve these diverse and abundant insect communities, which play a significant role in maintaining ecosystem health and complexity. Highlights: The study revealed a high diversity of insect species (H' index = 4.371) on Marsegu Island, highlighting its rich ecological complexity. The even distribution of insect species (E index = 0.931) underlines the balanced ecosystem, free from chemical interventions. Despite the high diversity, no species dominates the ecosystem, as reflected by a low dominance index (0.155), emphasizing the importance of species equality in maintaining ecosystem health. Keywords: Insect Diversity, Marsegu Island, Ecosystem Balance, Species Abundance, Dominance Index.